Complement Activation and its Prognostic role in Post‐cardiac Arrest Patients. (June 2014) - Jenei, Z. M.; Zima, E.; Csuka, D.; Munthe‐Fog, L.; Hein, E.; Széplaki, G.; Becker, D.; Karádi, I.; Prohászka, Z.; Garred, P.; Merkely, B.
Abstract Cardiac arrest causes generalized ischaemia/hypoxia, and subsequent resuscitation inflicts reperfusion injury, the pathology of which is not fully understood. Moreover, predicting the prognosis of comatose, post‐cardiac arrest patients is a complex clinical challenge. We hypothesized that the extent of complement activation might be a reliable predictor of mortality in this population. Forty‐six comatose cardiac arrest patients were enrolled into our prospective cohort study, conducted in a tertiary care university clinic. All subjects were cooled to 32–34 °C body temperature for 24 h and then allowed to rewarm to normothermia. All patients underwent diagnostic coronary angiography. On admission, at 6 and 24 h, blood samples were taken from the arterial catheter. In these, complement products (C3a, C3, C4d, C4, SC5b9 and Bb) were measured by ELISA in blood samples. Patients were followed up for 30 days; 22 patients (47.8%) died by the end of this period. We observed that complement activation (determined as the C3a to C3 ratio) was higher in non‐survivors than in survivors at each time point. In the multivariate Cox regression analysis, the C3a/C3 ratio determined 24 h after the initiation of therapeutic hypothermia predicted 30‐day mortality regardless of age, sex and the APACHE II score. Complement activation occurs in post‐cardiac arrest patients, and its extent correlates with 30‐day survival. The C3a/C3 ratio might prove useful for estimating the prognosis of comatose post‐cardiac arrest patients.